(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Solar energy is one of the renewable energy sources, with advantages such as environmental cleanliness and unlimited resources. However, the efficiency of solar panels depends on various factors, including the increase in their temperature. As the temperature rises, the electricity produced by the panels can decrease. Therefore, solar panel cooling systems play an important role in enhancing their efficiency. This paper discusses various methods of cooling solar panels, their advantages and disadvantages. Currently, solar energy is widely used as one of the most environmentally friendly and renewable energy sources. However, the efficiency of solar panels decreases with increasing temperature, as the increase in temperature reduces the electricity generated by the panels. This article provides a detailed analysis of methods for cooling solar panels, the possibilities of increasing their efficiency, and the calculation of water usage.